2019
DOI: 10.1371/journal.pone.0214803
|View full text |Cite
|
Sign up to set email alerts
|

Mal3 is a multi-copy suppressor of the sensitivity to microtubule-depolymerizing drugs and chromosome mis-segregation in a fission yeast pka1 mutant

Abstract: The cAMP-dependent protein kinase Pka1 is known as a regulator of glycogenesis, transition into meiosis, chronological aging, and stress responses in the fission yeast, Schizosaccharomyces pombe . We demonstrated here that Pka1 is responsible for normal growth in the presence of the microtubule-destabilization drug TBZ and proper chromosome segregation. The deletion of the pka1 gene resulted in the TBZ-sensitive phenotype and chromosome mis-segregation. We isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…The S. pombe pka1∆ strain shows a TBZ-sensitive phenotype and chromosome mis-segregation (Tanabe et al 2019). To determine the mechanism by which the loss of Pka1 induces the TBZ-sensitive phenotype, we focused on the transcription-related proteins that may be regulated by Pka1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The S. pombe pka1∆ strain shows a TBZ-sensitive phenotype and chromosome mis-segregation (Tanabe et al 2019). To determine the mechanism by which the loss of Pka1 induces the TBZ-sensitive phenotype, we focused on the transcription-related proteins that may be regulated by Pka1.…”
Section: Resultsmentioning
confidence: 99%
“…This assay was performed as previously described (Niwa et al 1986;Tanabe et al 2019). Two independent Ade + isolates of the wild type, pka1∆, tfs1∆, pka1∆ tfs1∆, pka1∆ rst2∆, and pka1∆ rst2∆ tfs1∆ strains, were analyzed for the stability of the mini-chromosome16 (Ch16) containing the ade6 gene, on the YE or adenine-limited EMMGU plates, in the presence or absence of 7.5 µg/mL TBZ.…”
Section: Mini-chromosomal Loss Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Gain of functional Pka1 partially recues growth defects of plb1∆, cyr1∆, and cyr1∆ plb1∆ under hypertonic stress conditions It has been shown that cgs1∆ rescued growth defects associated with the CaCl 2 -and TBZ-sensitive phenotypes of the cyr1∆ strain (Matsuo and Kawamukai 2017, Tanabe et al 2019). These results suggest that gain of functional Pka1 would rescue the stress-sensitive phenotype of cyr1∆, and also of plb1∆ if Plb1 is indeed upstream of Pka1 in the context of hypertonic stress response.…”
Section: Resultsmentioning
confidence: 99%
“…Through the promoter region of the stress starvation response element of S. pombe (STREP: CCCCTC), Rst2 regulates the expression of ste11, which encodes a transcription factor to regulate sexual development (Sugimoto et al 1991); fbp1, which encodes fructose-1,6-bisphosphatase (Hoffman and Winston 1990); and mug14, which encodes an adducin homolog (Inamura et al 2021). The cAMP/PKA pathway involves many cellular events, including transition to meiosis (Maeda et al 1994, Matsuo et al 2008, Wu and McLeod 1995, chronological aging (Roux et al 2006), stress response (Matsuo and Kawamukai 2017, Matsuo et al 2008, Stiefel et al 2004), glucose sensing (Byrne andHoffman 1993, Inamura et al 2021), proper chromosome segregation (Tanabe et al 2019), and proper microtubule structure maintenance (Tanabe et al 2020). function causes growth defects under a high concentration of KCl, the mechanism is yet to be identi ed.…”
Section: Introductionmentioning
confidence: 99%